2019
DOI: 10.32360/acmar.v52i1.33971
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho Zootécnico E Rendimento De Filé Do Robalo-Flecha Alimentado Com Diferentes Dietas Comerciais

Abstract: O objetivo do trabalho foi avaliar o efeito de diferentes dietas comerciais no desempenho zootécnico, nos índices organossomáticos e no rendimento de carcaça e filé do robalo- flecha. Diferentes rações comerciais para peixes carnívoros foram comparadas: Ração A (46,6% PB e 9,8% EE) e Ração B (60,6% PB e 13,3% EE), na engorda do robalo-flecha. Foram estocados juvenis de robalo-flecha com peso inicial de 355,40 ± 52,30 g, à densidade.de 15 peixes m-3 (5,33 ± 0,12 kg m-3), sob salinidade de 15 g L-1, em três tanq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The best specific growth rate obtained in this study was 0.82% day -1 reached in the summer of phase 1 (27.16°C), closer to the thermal comfort of the species (Winner et al, 2010), at the density of 20 fish m -3 . David et al (2019) found SGR values close to 0.84% day -1 for common snook at 28.59ºC in a recirculation system. Souza-Filho and Cerqueira (2003), in the experimental cultivation of juvenile snook (~ 60 g), with a temperature between 23.3 and 30.6 ºC, presented mean TCE values of 0.7% day -1 .…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…The best specific growth rate obtained in this study was 0.82% day -1 reached in the summer of phase 1 (27.16°C), closer to the thermal comfort of the species (Winner et al, 2010), at the density of 20 fish m -3 . David et al (2019) found SGR values close to 0.84% day -1 for common snook at 28.59ºC in a recirculation system. Souza-Filho and Cerqueira (2003), in the experimental cultivation of juvenile snook (~ 60 g), with a temperature between 23.3 and 30.6 ºC, presented mean TCE values of 0.7% day -1 .…”
Section: Methodsmentioning
confidence: 61%
“…Silvão and Nunes (2017) evaluated the effects of different dietary amino acid compositions for C. undecimalis and found a greater ability of snook to gain weight and increase nutrient retention when the dietary protein was of animal origin, such as protein from poultry by-product meal, with a composition of dietary amino acids more balanced in relation to that of fish muscle. David et al (2019), comparing diets without carbohydrates (60.59 g of crude protein) and with 15.25 g of carbohydrates (46.62 g of crude protein) in the fattening of common snook in a recirculation system, at an average temperature of 28.29 ºC, found an increase in weight by 22.20% for fish fed the diet without carbohydrates.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they are highly prized for the quality of their meat and valued for sport fishing (Passini et al 2019). Processing the fillet is easy, with high yield (~42%), and its market value is usually high (David et al 2019b;Cerqueira 2010).…”
Section: Snook (Centropomus Sp)mentioning
confidence: 99%
“…Researchers from Mexico reported the production of 800 g snook in 1 year (Sanchez-Zamora et al, 2003). Most of the experiments conducted with snook have been carried out in RAS, and aimed at understanding their reproductive biology (Passini et al 2018;2019), nutrition (Michelotti et al 2020;David et al 2019b), adequate stocking densities (Sanches et al 2011) and optimal water parameters, especially temperature and salinity (Michelotti et al 2018;Mello et al 2015). However, in the field of aquaponics, snooks are still unknown and no reports of their production in these systems were found.…”
Section: Snook (Centropomus Sp)mentioning
confidence: 99%